The role of common outer diffusion layer in the metal electrodeposition into template nanopores. (20th January 2021) - Bograchev, Daniil A.; Davydov, Alexey D.
Highlights: Metal electrodeposition into template nanopores. Uniform pore filling. Role of common outer diffusion layer. Controlled mass transfer and overpotential. Abstract: The effect of common outer diffusion layer in the vicinity of a template on the metal electrodeposition into the template pores is analyzed theoretically for two cases: (1) the template surface is uniformly accessible to the metal cations and (2) the electrolyte flows along the template surface. In the first case, the equation for the current density is obtained taking into account the common outer diffusion layer, the pore depth, and the kinetics of metal deposition. Under certain conditions, which can be determined from this equation, a common outer diffusion layer does not form, and its effect on the pore filling with the metal should not be taken into consideration. In view of the fact that the nanowire growth is a function of the electrolyte flow rate and kinetic parameters, in the second case, the dependences of inhomogeneity of pores filling with the metal on the liquid flow rate and kinetic parameters of electrochemical reaction are obtained. It is shown that, under the conditions of the formation of a common diffusion layer, the uniform pores filling requires controlled mass transfer in the electrolyte near the template and/or the lowest admissible overpotentials.